ТУРКИСТОНДА НОТАРИАТ ОРГАНЛАРИ ФАОЛИЯТИДАГИ ЎЗГАРИШЛАР - Жайнаров, О.Ҳ. (SCIENCE and SOCIETY, 2025)
The article, based on primary sources, reveals the changes that took place in the notarial system of Turkestan in 1917-1924, the state policy of the Soviet government in the field of notary services, the normative legal documents adopted in this sphere, the functions and powers of notarial bodies, as well as the activities of notaries.